The Iranian version of theory-based intention for cesarean section (IR-TBICS) scale: development and first evaluation - Naghibi, Seyed Abolhassan (BMC Pregnancy Childbirth, 2021)
BACKGROUND: The rate at which mothers experience a cesarean section in the absence of medical signs is growing worldwide. Women’s beliefs and intentions play an essential role in the request or choice of a delivery method. At present, there is no comprehensive, validated scale for assessing pregnant women’s beliefs about cesarean section in the Iranian population. This study was performed to develop and assess the validity and reliability of the intention-based cesarean section scale using the theory of reasoned action (TRA) constructs as a theoretical framework for measuring intention toward the selection of a delivery method. METHODS: In this cross-sectional validation study, 480 pregnant women were recruited from Sari, in northern Iran, through a multistage random sampling approach. Content validity was examined using the content validity index (CVI) and content validity ratio (CVR). Furthermore, both exploratory factor analyses (EFA) and confirmatory factor analyses (CFA) were applied to assess the construct validity of the developed scale. Reliability was measured by internal consistency and the intraclass correlation coefficient (ICC). Quality criteria for floor and ceiling effects were derived from existing guidelines and consensus within our research group. RESULTS: The results obtained from the factor analysis showed that the data were fit to the model (χ2 = 2298.389, P < 0.001). The TRA comprised 24 items assessing five domains, which described 62.46% of the common variance. The CFA showed a model with suitable fitness for the data. Cronbach’s alpha coefficient for the domains of the scale ranged from 0.609 to 0.843, and the ICC value ranged from 0.71 to 0.84, which is within the satisfactory range. The IR-TBICS scale had no floor or ceiling effect on the total score or any of the dimensions. CONCLUSIONS: The belief-based cesarean section scale appears to be a reliable instrument. It is considered suitable and can be applied in other research in Iran.